Analyzing different designs of liner shipping feeder networks: A case study. (February 2020) - Msakni, Mohamed Kais; Fagerholt, Kjetil; Meisel, Frank; Lindstad, Elizabeth
Highlights: Different network designs are studied for a liner shipping company. A feeder network design connects a major European port to local ports. A hub-and-spoke design allows transshipments at any local port. Both designs are modeled and solved based on realistic data. A discussion of which network design offering better costs is provided. Abstract: This paper proposes different network structures for a real liner shipping company to serve demands between Norwegian and European continental ports. The current practice of the shipping company deploys a feeder network where all routes depart from the European port. We study the impact of using a hub-and-spoke network that is composed of mother and daughter routes with the possibility of splitting pickups and deliveries. Computational studies carried out on problem instances based on realistic data show that significant cost reductions can in several cases be obtained by including the proposed network structure.